Environmental Contaminants Measurement, Modelling and Control (Energy, Environment, and Sustainability,, 2018)
This book addresses the measurement of environmental contaminants in water, air, and soil. It also presents modifications of and improvements to existing control technologies for remediation of environmental contaminants. It covers improved designs of wastewater systems and innovations in designing newer membranes for water treatment. In addition, it includes two separate sections on the modelling and control of different existing and emerging pollutants. It covers major topics such as: pharmaceutical wastes, paper and pulp waste, poly aromatic hydrocarbons, mining dust, bioaerosols, endosulphan, biomass combustion, and landfill design aspects. It also features chapters on environmental exposure and modelling of aerosol deposition within human lungs. The content of this book will be of interest to researchers, professionals, and policymakers whose work involves environmental contaminants and related solutions.